Justification Incorporated a Discursive Approach to Corporate Responsibility - Buddeberg, Eva (Ethical theory and moral practice, 2018)
Contrasting two standard models of corporate responsibilitythe so-called collectivist and individualist modelthis essay proposes a third option, namely, a discursive conception of responsibility and examines whether and how this conception can be applied to the corporate level. It does so by taking a careful look at one of the preconditions of individual discursive responsibility, i.e. discursive practical reason, and discussing how corporate agents can meet this precondition. Building on this new concept, the essay also offers a novel approach to justifying corporate responsibility by referring to an argument advanced by Rainer Forst stating that a fundamental human right to justification is the normative core of any kind of responsibility and combining it, in a second step, with an argument recently proposed by Philip Pettit and Christian List showing the impossibility of forming consistent group attitudes and beliefs as a function of the attitudes and beliefs of individual group members. Finally, this essay outlines certain preliminary conclusions about the incorporation of responsibility in a corporate context.